An assessment of the co-operattive enterprises that have benefitted from the Co-operative Insentive Scheme : a case study of the Matabane Co-operative in the Elias Motsoaledi Local Municipality in Limpopo Province of South Africa - Chabalala, Madimetja Matthews (University of Limpopo (Turfloop Campus), 2013)
The aim of this study was to assess the performance of co-operative enterprises that have benefited from the Co-operative Incentive Scheme (CIS). Matabane Co-operative in the Elias Motsoaledi Local Municipality in Sekhukhune District was used as a case study. Both primary and secondary data were used to analyse the performance of this co-operative. The primary data were collected through a pre-tested questionnaire, while electronic and non-electronic media were used to collect secondary data. Purposive sampling was used to select respondents and because the number of beneficiaries of the co-operative was too small (i.e., 36) all were selected for this purpose. Only tables were used to analyse data in this study. The results obtained showed that the level of participation of females and youth in co-operatives is minimal. With regard to the level of education, the study found that all beneficiaries were literate. Of the total membership, 31% had passed secondary education, 22% had tertiary qualifications, while those who had passed primary education constituted 47%. The study also found that the co-operative had generated 36 jobs. Of this number, 14% were awarded to females as compared to 86% among their male counterparts. The youth constituted only 8% of the co-operative membership as compared to the 92% of the adults and the elderly combined. With regard to income, the study found that the co-operative has managed to generate about R1,5 million, the majority of which comes from the sale of livestock and maize, namely 44% and 28% respectively. The following challenges were established by this study: lack of access to markets, lack of sufficient land space for production, lack of support from government, lack of access to water, shortage of proper skills, and the high cost of electricity. The following recommendations are therefore made to policymakers: · A budget for the payment of stipends to beneficiaries should be made available. The budget for the Community Work Programme (CWP) should be used for this purpose. · The municipality should provide a subsidy for electricity to the co-operative. · The Provincial Departments of Agriculture should provide the co-operative with adequate infrastructure. · LIBSA and other government agencies should ensure the provision of ongoing training in technical, project management, recordkeeping and financial management skills to the beneficiaries of the co-operative. · LIBSA should assist the co-operatives in identifying markets and in ensuring that their produce meets the required quality standards. The assurance is hereby given by this study that the productivity of co-operatives would be enhanced if these policies were implemented successfully.
Thesis (M.Dev) --University of Limpopo, 2013
Keywords: Co-operative incentive schemes; Cooperative enterprises; 658.047; Co-operative production -- South Africa; Co-operative associations